Marine Spatial Planning: spaces of protection and conservation, sovereignty and development - Violante, Alexandre; Figueiredo, Eurico de Lima (Conjuntura Austral, 2024)
The research question is whether Marine Spatial Planning is a tool, a methodology, a political process, or a combination of the three. Thus, this paper provides an understanding of Marine Spatial Planning: its origins, historical analysis, development, implications, and agendas, both globally and in Brazil. Concepts like politics, economics, law, the environment, geography, and strategy employed in ocean studies, which are always changing and being talked about in terms of how they work together and clash, are used as theoretical references. The research methodology employs an extensive bibliographical review of primary and secondary sources while prioritizing qualitative analytic methods. Conclusions are drawn about the international maritime community’s understanding of Marine Spatial Planning, specifically its role in enhancing ocean governance and restructuring state marine territories, as well as the intricate connections between these aspects. In Brazil, despite the relative priority of political power in the last decade, given Brazil’s international commitments, Marine Spatial Planning is still in its early stages, with not much expressed in effective domestic actions.